Cerebrovascular disease in Odessa region: epidemiology and prognosis - Oliynik, S. M. (Journal of Education, Health and Sport, 2015)
Oliynik S. M. Cerebrovascular disease in Odessa region: epidemiology and prognosis. Journal of Education, Health and Sport. 2015;5(8):236-242. ISSN 2391-8306. DOI 10.5281/zenodo.28211 http://dx.doi.org/10.5281/zenodo.28211 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A236-242 https://pbn.nauka.gov.pl/works/608388 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015. Cerebrovascular disease in Odessa region: epidemiology and prognosis Oliynik S. M. Odessa National Medical University, Odessa, Ukraine Abstract Cerebrovascular disease in Odessa region: epidemiology and prognosis. Oliynik S. M. Odessa National Medical University, Odessa, Ukraine The study was aimed to assess the incidence and prevalence of cerebrovascular diseases in Odessa Region. There was demonstrated that Odessa region has higher rates of CVD incidence and prevalence. The areas of high risk include Bessarabia and Dunabe districts belonging to the southern districts of Odessa region which are characterized with high environmental pollution and unfavorable mineral composition of drinking waters. The preventive strategies which could cut the current rate of CVD incidence are discussed. Key words: cardiovascular disease, stroke, epidemiology, Odessa region.